Research data for the literature review “Advances and future perspectives on electrodialysis for sustainable critical raw material refining” - Isaksson, Adam; Sundqvist Öqvist, Lena (Luleå University of Technology, 2026)
The dataset contains research data collected and structured for a literature review on electrodialysis for the sustainable extraction and recovery of critical raw materials. The material includes bibliographic information, extracted study data, search strategies, and screening data from literature searches conducted in Scopus and Web of Science.

The dataset consists of multiple CSV files, including: studies with bibliographic metadata and DOI, variables related to critical raw materials, electrodialysis techniques, membrane types, feed materials, methods, and results, documentation of search strategies and search strings, and a codebook with variable definitions.

The data were processed through manual screening, categorization, and extraction from published scientific articles. No specialized software is required to open the files beyond standard software capable of handling CSV files.

Datasetet innehåller forskningsdata som samlats in och strukturerats för en litteraturöversikt om elektrodialys för hållbar utvinning och återvinning av kritiska råmaterial. Materialet omfattar bibliografisk information, extraherade studiedata, sökstrategier och screeningdata från litteratursökningar i Scopus och Web of Science.

Datasetet består av flera filer i CSV-format, inklusive: studier med bibliografisk metadata och DOI, variabler relaterade till kritiska råmaterial, elektrodialystekniker, membrantyper, råmaterial, metoder och resultat, dokumentation av sökstrategier och söksträngar, codebook med definitioner av variabler.

Data har bearbetats genom manuell screening, kategorisering och extraktion från publicerade vetenskapliga artiklar. Inga specialiserade program krävs för att öppna filerna utöver standardprogram för CSV-filer.
Forskningsdata för litteraturöversikten “Advances and future perspectives on electrodialysis for sustainable critical raw material refining”
Keywords: rare earth metals; sällsynta jordartsmetaller; literature surveys; litteraturöversikter; circular economy; cirkulär ekonomi; hydrometallurgy; hydrometallurgi; electrodialysis; elektrodialys; platinum-group metals; platinagruppens metaller; critical raw materials; kritiska råmaterial; battery metals; batterimetaller; ion exchange membrane; permselektivt membran; Chemical Engineering; Kemiteknik; Environmental Engineering; Naturresursteknik; Separation Processes; Separationsprocesser